Evaluasi Kinerja Sistem Distribusi Perusahaan Batubara dengan Adanya Penambahan Coal Terminal - Sri Gunani Partiwi; I.K. Gunarta; Mohammad Hidayatullah (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
The company ‘X’ plans to build a new coal terminal as the strategy to take over the infrastructure and improve the service level for the customers. This idea was triggered by the projection of future local demand due to the Mega Project (10,000 MegaWatt) and the financial capability of the company are also became the background of developing the new coal terminal. The objective of this research is to analyze the performance of distribution system with the developmentof new port and stockpile. The performance measure are reliability, cost, responsiveness, and flexibility of the distribution system. The main methods using in this research are system modelling and simulation. The first step for doing this research is developing existing distribution system model and the new model (with port and stockpile). Running the simulation of that model was done by designing the two scenario, i.e. using the fixed demand of product from PLTU and increasing of demand of products doe to the development of new power plant. The results from simulation and performance measurement for both distribution model show that the founding of new coal terminal for the company will affect positively to the performance of its distribution system.